Size spectroscopy of porous glasses and porous glasses with metal nanoparticles using UV–VIS and X-ray radiation - Ovechko, Volodymyr; Schur, Olexander (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
UV–VIS and X-rays radiation were used for porous silica (PS) and porous silica with Ag nanoparticles investigations. It has been shown that XRD experiment gives information about the correlation function of heterogeneity in PS. Well-known plasmon resonance in UV spectral region was applied for the concentration and mean diameter of the metal particles determination.
Optica Applicata, Vol. 35, 2005, nr 4, s. 735-743
Keywords: optyka; porous silica; X-ray diffraction (XRD); plasmon; silver nanoparticles